H-beta zeolite: an efficient, reusable catalyst for one-pot synthesis of isatins from anilines - Raj, I. Victor Paul; Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (Acta Chimica Slovenica, 2010)
We describe a simple and highly efficient procedure for the single-step preparation of isatins from the commercially available anilines using H-beta zeolite as a truly heterogeneous catalyst. H-beta zeolite is readily separated from reaction mixture by simple filtration and reused several times without considerable loss of activity.
Keywords: Anilines; H-beta zeolite; heterogeneous catalyst; isatins